2022
DOI: 10.1007/s11205-022-02890-0
|View full text |Cite
|
Sign up to set email alerts
|

Who Received Informal Social Support During the First COVID-19 Lockdown in Germany, and Who Did Not? The Role of Social Networks, Life Course and Pandemic-Specific Risks

Abstract: In this article, we study the receipt of informal support during the first wave of the COVID-19 pandemic in Germany. The containment measures have had various, far-reaching consequences for the wellbeing of people, creating demands for economic, practical, and emotional support—even among individuals who hitherto were not in need of support. Existing research has shown substantial levels of informal support during the pandemic, often based on individuals’ existing social networks, but has predominantly taken t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 67 publications
0
12
0
Order By: Relevance
“…Finally, our study focusses primarily on the supply side of instrumental help and the determinants of providing help as we were primarily interested in better understanding how and to what degree the COVID-19 pandemic and its accompanying epidemiological control measures affected the provision of help to others outside the own household (the help provided in the multigenerational households was not included in the analyses). Further research should also look more closely at the demand side and determinants of receiving help (for example the correlation between health status, living alone and reciprocity of the intergenerational exchange during the pandemic; see, e.g., Bertogg and Koos, 2022 for Germany). Regarding reciprocity, it could be argued that the sequence of receiving and providing help is of relevance.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, our study focusses primarily on the supply side of instrumental help and the determinants of providing help as we were primarily interested in better understanding how and to what degree the COVID-19 pandemic and its accompanying epidemiological control measures affected the provision of help to others outside the own household (the help provided in the multigenerational households was not included in the analyses). Further research should also look more closely at the demand side and determinants of receiving help (for example the correlation between health status, living alone and reciprocity of the intergenerational exchange during the pandemic; see, e.g., Bertogg and Koos, 2022 for Germany). Regarding reciprocity, it could be argued that the sequence of receiving and providing help is of relevance.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that older adults' level of intergenerational interactions were more likely to increase in countries with more stringent measures (Vergauwen et al, 2022). These increases in support are likely responses to intensi ed pre-existing needs for support as well as newly created needs among older adults who were previously not relying on external support (Bertogg & Koos, 2022).…”
Section: Effect Of Changes In Intergenerational Support On Depressive...mentioning
confidence: 96%
“…Therefore, in analyzing certain past events and experiences…[it may be beneficial to] "follow groups of individuals into the future getting a continuous record of experiences as they occur" (Newman & Newman, 2016, p. 201). Life course theory helps to pin point vulnerable groups that need support, by following people's experiences between various stages (i.e., middle adulthood to older adulthood) (Bertogg & Koos, 2022). Life transitions are a part of these trajectories by explaining "the beginning or close of an event, role relationship, or developmental stage" (Newman & Newman, 2016, p. 202).…”
Section: Life Course Theorymentioning
confidence: 99%
“…Indeed, behavior characteristics on an individual level may be influenced by people with whom they have a close relationship. An example of "linked lives" of a married couple (partner dyads) can be through sharing healthy behavior mechanisms and sharing resources (such as exchanging emotional support) (Ang, 2021;Bertogg & Koos, 2022). In trying to understand patterns of behavior over time, life course theory can be applicable by looking at actions and thoughts related to outside changes within the environment and aiming to understand differences in how groups of people perceive events in life (Alwin, 2012).…”
Section: Linked Lives and Interdependencementioning
confidence: 99%
See 1 more Smart Citation